Multi-product pricing: Theory and evidence from large retailers - Marco Antonio Bonomo; Carlos Viana de Carvalho; Oleksiy Kryvtsov; Sigal Ribon; Rodolfo Rigato (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2021)
We study a unique dataset with comprehensive coverage of daily prices in large multi-product retailers in Israel. Retail stores synchronize price changes around occasional "peak" days when they reprice around 10% of their products. To assess aggregate implications of partial price synchronization, we develop a new model in which multi-product firms face economies of scope in price adjustment, and synchronization is endogenous. Synchronization of price changes attenuates the average price response to monetary shocks, but only high degrees of synchronization can substantially strengthen monetary non-neutrality. Our calibrated model generates as little monetary non-neutrality as in Golosov and Lucas (2007).
Keywords: D21; D22; E31; E52; L11; 330; Ination; Prices; Multi-product pricing; Synchronization of prices; Menu cost; Monetary non-neutrality